A macrobending-based optical fiber inclinometer to measure the ground tilt in the depth which forms a positive and negative angle to the gravity axis. (March 2019) - Bayuwati, D; Mulyanto, I; Suryadi; Widiyatmoko, B; Chandra, T G; Kurniawan, E
Abstract: This paper discusses an optical fiber inclinometer to measure ground tilt in soil depth, which forms an angle between vertical axis to the gravity axis. The macrobending based-inclinometer consists of a laser source system, fiber cable, geotechnical cylinder; rolling wheels and pressing levers each sitting on top and bottom support; stainless steel rope, cylinder loads, light detection and output data. The stabilized laser was split into four by an optical coupler into ports of sensor fiber 1, sensor fiber 2, reference fiber and one backup port, then entering into a geotechnical cylinder housed in a standard geotechnical pipe. If there is instability of the soil condition resulting in a tilting of the soil surface, the geotechnical cylinder changes its position to form an angle to the gravity axis, furthermore the active pressure lever will suppress the optical fiber sensor. At this stage, the optical fiber will undergo a macro bending resulting in a change of its output. This intensity change output will correspond to the change of the angle for each tilting direction (left and right). The fiber inclinometer has a measurement range of 10° for both direction with accuracy of 0.5°.